Passive Clearing and 3D Lightsheet Imaging of the Intact and Injured Spinal Cord in Mice - McCreedy, Dylan A.; Jalufka, Frank L.; Platt, Madison E.; Min, Sun Won; Kirchhoff, Megan A.; Pritchard, Anna L.; Reid, Shelby K.; Manlapaz, Ronald; Mihaly, Eszter; Butts, Jessica C.; Iyer, Nisha R.; Sakiyama-Elbert, Shelly E.; et al. (Frontiers in Cellular Neuroscience, 2021)
The spinal cord contains a diverse array of sensory and motor circuits that are essential for normal function. Spinal cord injury (SCI) permanently disrupts neural circuits through initial mechanical damage, as well as a cascade of secondary injury events that further expand the spinal cord lesion, resulting in permanent paralysis. Tissue clearing and 3D imaging have recently emerged as promising techniques to improve our understanding of the complex neural circuitry of the spinal cord and the changes that result from damage due to SCI. However, the application of this technology for studying the intact and injured spinal cord remains limited. Here we optimized the passive CLARITY technique (PACT) to obtain gentle and efficient clearing of the murine spinal cord without the need for specialized equipment. We demonstrate that PACT clearing enables 3D imaging of multiple fluorescent labels in the spinal cord to assess molecularly defined neuronal populations, acute inflammation, long-term tissue damage, and cell transplantation. Collectively, these procedures provide a framework for expanding the utility of tissue clearing to enhance the study of spinal cord neural circuits, as well as cellular- and tissue-level changes that occur following SCI.